2005
DOI: 10.1002/eji.200525998
|View full text |Cite
|
Sign up to set email alerts
|

FcγRII-dependent sensitisation of natural interferon-producing cells for viral infection and interferon-α responses

Abstract: Natural interferon-producing cells (NIPC), also called plasmacytoid dendritic cells, are the most potent producers of IFN-a in response to viral and bacterial components,s serving an important function in innate immune defences. The present work demonstrates that NIPC responsiveness can be primed by immunisation, increasing their capacity to produce IFN-a after viral infection. NIPC isolated from pigs immunised against classical swine fever virus (CSFV), a member of the Flaviviridae, were more receptive to vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
46
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 35 publications
7
46
1
1
Order By: Relevance
“…These data also showed that cDC, unlike pDC, disappeared permanently from blood after infection, preventing an efficient turn-over of these DC subset in the spleen. This observation was in agreement with in vitro studies showing that mo-DC functionalities were more affected than NIPC by CSFV infection [4,13]. DC maturation after viral stimulation, demonstrated by down-regulation of CD1a expression and up-regulation of CD80/86 expression [12,15,31], was observed in both DC types.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These data also showed that cDC, unlike pDC, disappeared permanently from blood after infection, preventing an efficient turn-over of these DC subset in the spleen. This observation was in agreement with in vitro studies showing that mo-DC functionalities were more affected than NIPC by CSFV infection [4,13]. DC maturation after viral stimulation, demonstrated by down-regulation of CD1a expression and up-regulation of CD80/86 expression [12,15,31], was observed in both DC types.…”
Section: Discussionsupporting
confidence: 91%
“…In blood, jagged variations in frequencies of pDC expressing cytokines illustrated the pDC turnover presented above. These results were in agreement with cytokine production by in vitro CSFV-infected NIPC [4,42]. Moreover, porcine blood-isolated NIPC secreted IFN-α, TNF-α and IL-12, but not IL-10, after CpGoligonucleotide stimulation [20].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Despite this, only a few studies have investigated their actual role in the immune response. These studies defined pDC as vital cellular components in the initiation of NK and T cell responses to viral Ags (11,12), effectors in the memory response to microbial Ags, where Ag-specific IgG is a prerequisite for pDC activation (13,14), important mediators of transplant tolerance (15)(16)(17)(18), and inducers of T regulatory cells (19,20).…”
mentioning
confidence: 99%